DERECHO HEREDADO, MONARQUIA ADQUIRIDA: APORTACIONES DEL QUINIENTOS A LA CONFIGURACION DEL REGIMEN POLITICO ESPAÑOL - Poncela González, Ángel (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
The defence of marriage on the part of theorists like Rodrigo Sánchez de Arévalo, Alfonso de Madrigal, «El Tostado» and Alfonso de la Torre, condemning the practice of any form of polygamy is, quite apart from the moral and religious implications, an instrument legitimisation of the ruling government. In this way the theorists of the Spanish renaissance ensured the continuation of the monarchy, and with it the social order of the estates.
Keywords: Polygamy; Monarchy; Marriage; City